Eksplorasi Pose dalam Pemotretan Model Melalui Kajian Visual Relief Karmawibhangga - Noor Latif CM (Bina Nusantara University, 2015)
Karmawibhangga Relief panel located at the foot of Borobudur is a relic of the visual artifacts that contains fragments of past life with a very high historical value. 160 Karmawibhangga panels tell the reality of people's lives at the time wrapped with a moral message plight. The relief provides a lot of visual references to be excavated and reconstructed again for the benefit of the creative industries today. This research digged one small part of the masterpieces of the past through photography. Understanding visual artists who create these reliefs will be beauty in the show gestures in building a very interesting story to be re-examined. Visual communication through gestures in relief Karmawibhangga enables new assumptions about body language dialect differences to current conditions. Through model genre photography, it is very useful in connection with the development of local nuanced scientific photography. Efforts to develop the traditions and culture through new media are expected to be creative commodity with a very strong product differentiation.